2020
DOI: 10.1108/tpm-03-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Collective orientation and its implications for coordination and team performance in interdependent work contexts

Abstract: Purpose This paper aims to explore the influence of collective orientation (CO) on coordination and team performance for interdependently working teams while controlling for person-related and team variables. Design/methodology/approach A total of 58 two-person-teams participated in a simulation-based firefighting task. The laboratory study took 2 h for each team. The effects of CO in tasks of increasing complexity were investigated under the consideration of control variables, and the relations between CO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 89 publications
2
17
2
Order By: Relevance
“…According to Hagemann et al (2021), collectivist orientation (CO) refers to "an attitude that enhances team performance through coordination, evaluation and consideration of task inputs from other team members while performing a team task". Oyserman et al (2002) posited that collectivism is the assumption that binds and mutually obligates individuals toward common interests.…”
Section: Collectivist Orientation and Risk Governancementioning
confidence: 99%
“…According to Hagemann et al (2021), collectivist orientation (CO) refers to "an attitude that enhances team performance through coordination, evaluation and consideration of task inputs from other team members while performing a team task". Oyserman et al (2002) posited that collectivism is the assumption that binds and mutually obligates individuals toward common interests.…”
Section: Collectivist Orientation and Risk Governancementioning
confidence: 99%
“…Because of their identification with the group, individuals with high CO are more engaged in support behaviors to accomplish team tasks (Dierdorff et al, 2011). Collectively oriented members increasingly engage in interaction behaviors, which amends team performance (Driskell et al, 2010;Hagemann et al, 2021). CO has been shown to be advantageous for complex (nonroutine) situations, as teams are better able to coordinate their actions (Hagemann et al, 2021).…”
Section: Input: Individual-related Factorsmentioning
confidence: 99%
“…Collectively oriented members increasingly engage in interaction behaviors, which amends team performance (Driskell et al, 2010;Hagemann et al, 2021). CO has been shown to be advantageous for complex (nonroutine) situations, as teams are better able to coordinate their actions (Hagemann et al, 2021). We assume that experience and acceptance with WFH and CO are associated with team success in the instant adjustment to virtual teams.…”
Section: Input: Individual-related Factorsmentioning
confidence: 99%
“…Research found that collectivist orientation (CO) is an important factor that impacts an employee's behaviors to greater extent (Zulfiqar et al, 2019). CO can be defined as views about one's self, of how his goals and the goals of the group he works in are interdependent (Hagemann et al, 2020). One's perception about the relationship with other group memebers and group cohesiveness plays a key role in driving human behaviors at work (Hagemann et al, 2020;Hofstede, 2001).…”
Section: Introductionmentioning
confidence: 99%